Governance, policy, and health systems responses to the COVID-19 pandemic in Thailand: a qualitative study - Titiporn Tuangratananon; Nattadhanai Rajatanavin; Sarayuth Khuntha; Salisa Rittimanomai; Nima Asgari-Jirhandeh; Viroj Tangcharoensathien (Frontiers Media S.A., 2024)
BackgroundSince 2020, Thailand has experienced four waves of COVID-19. By 31 January 2022, there were 2.4 million cumulative cases and 22,176 deaths nationwide. This study assessed the governance and policy responses adapted to different sizes of the pandemic outbreaks and other challenges.MethodsA qualitative study was applied, including literature reviews and in-depth interviews with 17 multi-sectoral actors purposively identified from those who were responsible for pandemic control and vaccine rollout. We applied deductive approaches using health systems building blocks, and inductive approaches using analysis of in-depth interview content, where key content formed sub-themes, and different sub-themes formed the themes of the study.FindingsThree themes emerged from this study. First, the large scale of COVID-19 infections, especially the Delta strain in 2021, challenged the functioning of the health system's capacity to respond to cases and maintain essential health services. The Bangkok local government insufficiently performed due to its limited capacity, ineffective multi-sectoral collaboration, and high levels of vulnerability in the population. However, adequate financing, universal health coverage, and health workforce professionalism and commitment were key enabling factors that supported the health system. Second, the population's vulnerability exacerbated infection spread, and protracted political conflicts and political interference resulted in the politicization of pandemic control measures and vaccine roll-out; all were key barriers to effective pandemic control. Third, various innovations and adaptive capacities minimized the supply-side gaps, while social capital and civil society engagement boosted community resilience.ConclusionThis study identifies key governance gaps including in public communication, managing infodemics, and inadequate coordination with Bangkok local government, and between public and private sectors on pandemic control and health service provisions. The Bangkok government had limited capacity in light of high levels of population vulnerability. These gaps were widened by political conflicts and interference. Key strengths are universal health coverage with full funding support, and health workforce commitment, innovations, and capacity to adapt interventions to the unfolding emergency. Existing social capital and civil society action increases community resilience and minimizes negative impacts on the population.